Tuning of Poly‐S‐Nitrosated Human Serum Albumin as Superior Antitumor Nanomedicine. Issue 7 (20th May 2014) - Ishima, Yu; Fang, Jun; Kragh‐Hansen, Ulrich; Yin, Hongzhuan; Liao, Long; Katayama, Naohisa; Watanabe, Hiroshi; Kai, Toshiya; Suenaga, Ayaka; Maeda, Hiroshi; Otagiri, Masaki; Maruyama, Toru
<x xml:space="preserve">Abstract</x> Macromolecules have been developed as carriers of low‐molecular‐weight drugs in drug delivery systems (DDS) to improve their pharmacokinetic profile or to promote their uptake in tumor tissue via enhanced permeability and retention (EPR) effects. We have previously demonstrated that poly‐nitric oxide (NO) conjugated human serum albumin (Poly‐SNO‐HSA) has the potential to be a DDS carrier capable of accumulating NO in tumors. However, the stability of Poly‐SNO‐HSA in the circulation has to be improved, and its optimal molecular size for using the EPR effects has to be evaluated. In the present study, we performed two tuning methods for refining Poly‐SNO‐HSA, namely, pegylation and dimerization. We observed that pegylation enhanced the stability of Poly‐SNO‐HSA both in vitro and in vivo, and that dimerization of Poly‐SNO‐HSA enhanced the antitumor activity via more efficient delivery of NO in Colon 26 tumor‐bearing mice. Intriguingly, dimerization resulted in a 10 times higher antitumor activity. These data suggest that pegylation and dimerization of Poly‐SNO‐HSA are very important tuners to optimize NO stability and accumulation, and thereby effect, in tumors. Thus, polyethylene glycol‐Poly‐SNO‐HSA dimer seems to be a very appealing and safe NO carrier and thereby a strong candidate as an antitumor drug in future development of cancer therapeutics. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2184–2188, 2014